Mythology as the guardian of the authenticity of the angkola Tor-tor dance in traditional wedding ceremonies in the modern era - Ramdiana Ramdiana; Novysa Basri; Tengku Hartati; Raihana Salsabila Dalimunte (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
This study explores the role of mythology in maintaining the authenticity of the Angkola Tor-tor Dance in contemporary wedding traditions. By examining the phenomena of cultural commodification, simplification of movements, and the use of digital media that can obscure the meaning of rituals, this study explores how mythological narratives, ancestral symbols, and ceremonial structures serve as normative references and sources of legitimacy for these practices. This study applies a qualitative methodology using cultural mythology and ethnochoreology. The methods used include literature review, participant observation in several Angkola wedding ceremonies, and in-depth interviews with traditional leaders and artists. The research findings reveal that mythology, particularly the story of the origins of the Angkola Tor-tor, the relationship between humans and ancestral spirits, and the value of respect for the clan, serves as a framework of meaning that maintains consistency between form (movement, costume, formation) and function (prayer, respect, social cohesion). In the context of modernization, innovation is still permitted as long as it does not violate the main mythological principles: the order of presentation, the ethics of family interactions, and the symbolic meaning of attributes. Performance curation provides an understanding of the ritual context, and the use of digital media to document accurate interpretations. The implications of this research emphasize that the power of mythology is not only about the romanticism of the past, but also a flexible cultural capital to negotiate the identity, customary authority, and aesthetic sustainability of Tor-tor Angkola in the current cultural context.